Automation and Offshoring in Durable Goods Manufacturing: An Indiana Case Study. Issue 1 (February 2019) - Slaper, Timothy F.
The loss of manufacturing jobs is largely attributed to either offshoring or automation. Using state-level data from the Annual Survey of Manufactures and unit record administrative data from the Indiana Department of Workforce Development, we determine the drivers of durable goods manufacturing employment losses in Indiana. We test a simple model that explains changes in industry production employment by changes in output, wages, intermediate input consumption, productivity, capital-to-labor ratios, or a proxy related to these explanatory variables. Using the unit record data, the authors assess the consequences of large layoff events on the wages of those who remain employed at a particular manufacturing establishment. The data suggest that offshoring was the primary driver for employment losses and productivity gains in Indiana, not automation. We also find that average wages for workers at establishments that experienced large redundancy events rose for those workers who remained after large layoff events.